Peran Bidang Umum Kepegawaian Serta Perencanaan dan Evaluasi dalam Mendukung Kinerja Badan Keuangan dan Aset Daerah Kota Palangka Raya - Dea Yuni Sepita Sinaga; Aprilita Aprilita; Ni Nyoman Tri Astuti; Tesalonika Tesalonika (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study discusses the role of the General Personnel and Planning Division in supporting the performance of the Regional Financial and Asset Agency of Palangkaraya City. The method used is descriptive qualitative, involving interviews and observation. The findings show that the General Personnel Division supports personnel administration and employee management, while the Planning Division supports work effectiveness and efficiency through coordination, monitoring, evaluation, and task distribution. The main obstacles are delayed data collection, limited qualified human resources, formalistic work culture, and changing regulations.